Progam Isi Piring Dengan Nutrisi Bolu Singkong Atasi Stanting di Desa Sukadana Kabupaten Lombuk Utara - Made Sutha Yadnya; Misbahhudin Misbahhudin; I K Wirajati; Abdullah Zaenuddin; Bulkis Kanata; I A Sri Adnyani (Jurnal Gema Ngabdi, 2023)
The addition of nutrition is focused on the main activities for stunting in Sukadana Village, Bayan District, North Lombok Regency, a village that has abundant resources such as honey, cassava, fish, cashew nuts, corn, and so on. One is cassava. Villages have the opportunity to provide innovation in increasing agricultural output, such as innovating cassava, innovating cassava agricultural products, and marketing outreach to MSMEs in Sukadana Village. It is hoped that with this, local residents can be moved to continue businesses related to these two products. Increasing processed of nutrition cassava by processing it by making sponge cake an additional food containing eggs. The shape of cassava cake is made in various ways. The results of the processing have been practiced and consumed by the people of Sukadana Village. To maintain quality and content, it is disseminated with the assistance of BKKBN in terms of speakers and funds.